2022
DOI: 10.1177/10732748221075468
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Influences the Response of Glioblastoma Cells to Temozolomide and Dexamethasone

Abstract: Objective Current research indicates that weakness of glucose metabolism plays an important role in silencing of invasiveness and growth of hypoxic tumors such as GBM. Moreover, there are indications that DXM, frequently used in treatment, may support GBM energy metabolism and provoke its recurrence. Methods We carried out in vitro experiments on the commercial T98G cell line and two primary GBM lines (HROG02, HROG17) treated with TMZ and/or DXM in physiological oxygen conditions for GBM (2.5% oxygen) and for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…Это исследование подчеркивает важность выявления альтернативных агентов, таких как антагонисты VEGF, для лечения отеков у пациентов с глиомами головного мозга [20]. В основе неэффективной терапии с использованием дексаметазона могла лежать и его способность поддерживать энергетический метаболизм глиом, что обеспечивало возможность их повторного роста [21].…”
Section: Discussionunclassified
“…Это исследование подчеркивает важность выявления альтернативных агентов, таких как антагонисты VEGF, для лечения отеков у пациентов с глиомами головного мозга [20]. В основе неэффективной терапии с использованием дексаметазона могла лежать и его способность поддерживать энергетический метаболизм глиом, что обеспечивало возможность их повторного роста [21].…”
Section: Discussionunclassified
“…Given that metabolic signalling pathways can be implemented in the discrete module and the macroscopic response quantified by the continuum module, the proposed framework can be further utilized to investigate metabolism-targeted cancer therapies. For instance, hGBMs exhibit an aberrant glucose metabolism that could be targeted as a potential therapeutic strategy [59]. Future research directions include co-culturing hGBMs tumoroids with healthy neurons to mimic the microenvironment and interactions of both tumor and brain tissue.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For performing protein pro le assay, three lines were cultured according to the previously described method [13]. When the con uency reached about 97%, TMZ was added (or not added in control group) to the culture for 24 hrs and GBM lines were incubated in hypoxia conditions (2.5% oxygen).…”
Section: Protein Analysismentioning
confidence: 99%
“…Since our previous study performed on commercial T98G and primary (HROG02, HROG17) human GBM cell lines showed differences in sensitivity of cells to TMZ, induced by changes of glucose and oxygen concentration in culture medium [13], we decided to investigate if and which differences in proteome pro le of analyzed GBM lines could be correlated with this effect. We compared TMZ effects on protein expression in commercial T98G cell line, a GBM lines derived from a patient not treated after resection (HROG02) and a patient with recurrence (HROG17), looking for common or characteristic markers speci c for these lines.…”
Section: Introductionmentioning
confidence: 99%